Evaluation of a dipstick enzyme-linked immunosorbent assay for detection of antibodies to dengue virus. - Wu, S J (1997)
Accurate serological confirmation of dengue (DEN) infection is difficult, because simple reliable assays for the detection of DEN antibodies are not available. To address this problem, a dipstick enzyme-linked immunosorbent assay (ELISA) was evaluated. The dipstick contained dots of serially diluted DEN 2 antigen. To detect immunoglobulin G (IgG), the dipstick was processed through four reaction cuvettes containing test serum, enhancer, enzyme-conjugated anti-human IgG and IgM antibody, and substrate. Total assay time was 45 min. To detect IgM, the serum was passed through a protein G device to remove IgG. The dipstick was then processed as before, except that the incubation times were longer and enzyme-conjugated anti-human IgM was used. The total assay time was 3 h. The dipstick ELISA results were compared with results from microplate ELISA. The IgG dipstick ELISA showed a sensitivity of 95.2% and a specificity of 100% compared to an IgG microplate ELISA with serum samples from 125 individuals living in an area in which DEN is endemic. In tests with 75 serum samples from patients with clinically suspected acute DEN infections, the IgM dipstick ELISA showed a sensitivity of 97.9% and specificity of 100% compared to those of an IgM antibody capture microplate ELISA. These results showed that the dipstick ELISA was a sensitive and specific test for the detection of either DEN IgM or IgG in human serum. The dipstick ELISA was also shown to be useful for detecting seroconversions to DEN IgM or IgG in paired serum samples from 20 patients with virus isolation-confirmed acute DEN infections.